PENGARUH BYSTANDER EFFECT, GAYA HIDUP, MORAL INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Rita, Mariana Fantina; Muanifah, Suciati (Publika Citra Media, 2025)
This study aims to determine and provide empirical evidence regarding the influence of the bystander effect, lifestyle, individual morals, on the tendency of accounting fraud. by selecting the object or place of research in the Wotan Ulumado sub-district, East Flores, East Nusa Tenggara. This study uses a quantitative research method, with a sample of 99 respondents, and the sampling technique used is the sampling technique in this study is probability sampling using simple random sampling stating simple (simple) because the sampling of population members is carried out randomly without considering the existing strata. The results of the study indicate that the bystander effect, lifestyle, individual morals simultaneously influence the tendency of accounting fraud. However, partially individual morals do not affect the tendency of accounting fraud.